Pengaruh Kerja Shift terhadap Kadar Glutamic Acid Decarboxylase 65 (GAD65) dalam Serum Darah - Imam Cahyo Murwidi (Politeknik Kesehatan Tanjung Karang, 2018)
This study was to know shift work influences to increases levels of Glutamic Acid Decarboxylase 65 (GAD65) in the blood serum which is a marker of pancreatic beta cell destruction.The study method was quasi-experimental with the non-randomize pretest-posttest control group design. Subjects in this study were nurses at the R.A. Kartini Jepara hospital, female, aged 25 to 50 years, BMI 18.5 to 24.9, a work period of more than three years, did not have a routine or schedule a job outside the main working and randomize blood glucose less than 200 mg/dl. The sample size was 20 shift worker nurses and 20 non-shift worker nurses. GAD65 examination with ELISA method. The data study was analyzed with Wilcoxon test, paired t-test and independent t-test.The study results showed significant difference (p Wilcoxon test = 0.04) between the mean levels of GAD65 shift workers group pretest (0.189 ± 0.180 ng/ml) with posttest (0.334 ± 0.334 ng/ml). Not significant (p Paired t-test = 0.081) difference between the mean levels of GAD65 non-shift worker group pretest (0.326 ± 0.284 ng/ml) with posttest (0.218 ± 0.164 ng/ml). Significant (p Independent t-test = 0.008) difference between the mean delta GAD65 shift workers group (0.307 ± 0.145 ng/ml) with the non-shift workers group (- 0.107 ± 0.261 ng/ml).It can be concluded that shift work can increase GAD65 levels in blood serum but still within the normal range.